Peningkatan Pengetahuan Siswa Melalui Edukasi Tentang Bahan Pengawet Yang Berbahaya Pada Makanan Jajanan Di SMAN 14 Makassar - Muawanah Muawanah; Dewi Arisanti; Rahmawati Rahmawati; Waode Rustiah (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
Presevatives are compounds that can inhibit and stop the process of fermentation, acidification, or other forms of damage, and protect foodstuffs from spoilage. According to the Regulation of The Minister of Health of the Republic of Indonesia No. 033 of 2012 concerning additives that are prohibited from being used in food are boric acid (borax), formalin, salicylic acid, and others. These dangerous preservatives are still widely used by manufacturers in the food industry, including snacks at schools. Preservatives that are prohibited for use in food can have a negative impact on heallth, namely causing nausea, vomiting, dizziness, irritation, allergies, and are carcinogenic. The problem faced is that there are still traders or manufacturers who use harmful preservatives in snacks at school. Therefore, counseling activities were carried out regarding increasing knowledge of the use of harmful preservatives in street food at SMA Negeri 14 Makassar. The method used is the approach method through lectures, disscussions and evaluations. The results of this service activity regarding students’knowledge of the types of preservatives that are dangerous in snacks at school, the characteristics of foods that contain harmful preservatives and their impact on health are ver good. Thus, it can be concluded that this community service activity has increased students’ knowledge about harmful preservatives in snacks at school.